Oral focal mucinosis of the mandible in an adolescent patient. Issue 12 (17th December 2019) - Cho, Jason J; Shupak, Raymond P; Michaels, Caroline
Abstract : Oral focal mucinosis (OFM) is the rare oral manifestation of cutaneous focal mucinosis. It is a diagnosis made histopathologically, as OFM remains clinically similar to other more common oral lesions, and radiographs do not provide any diagnostic information. This case is a report of a teenage female with left mandibular involvement of an elevated, rounded, asymptomatic, mucosa-coloured lesion in the facial and lingual gingiva between her left first and second mandibular molars. The cause was unclear, although the patient stated that she may have sustained a laceration in that area several months prior. An incisional biopsy revealed histopathological findings consistent with OFM, and complete surgical excision of the lesion was performed under a general anaesthetic, with no signs of recurrence for 2 months. The histological, clinical and accepted treatment methods on OFM will be discussed. Clinicians, including those serving paediatric populations, should consider OFM in their differential diagnoses when evaluating gingival lesions.